THE USE OF TOTAL PHYSICAL RESPONSE TECHNIQUES IN TEACHING ENGLISH AT PRIMARY SCHOOL - Arzieva, B.A.; Ismailova, D.U. (ILIM hám JÁMIYET, 2017)
The article deals with the study of using the method. Total Physical Response in teaching English in secondary school. There are considered different types of TPR technology, methods of their use and roles of the teacher and pupils. An important role in using TPR play the teacher’s voice, actions, gestures and objects of the classroom, sound and visual materials.